Peningkatan Kompetensi Melaksanakan Pakem dengan Lesson Study berbasis KKG pada Guru Kelas di SDN 4 Sempol Kecamatan Pagak Kabupaten Malang Semester I tahun pelajaran 2019/2020 - Handayani, R. Indah Handayani (Universitas Nahdlatul Ulama Pasuruan, 2022)
In an effort to help solve the problem of the low competence of teachers in carrying out Active, Creative, Effective, and Fun Learning (PAKEM) in Class V, the researchers offer a form of professional coaching for educators with KKG-based Lesson Study. It is suspected that the KKG-based Lesson Study provides a process for collaborating and designing learning and evaluating the success of teaching strategies that have been implemented as an effort to improve the process and student learning outcomes. The purpose of this School Action Research is to improve the competence of implementing PAKEM with KKG-Based Lesson Study for Class Teachers at SDN 4 Sempol, Pagak District, Semester I for the 2019/2020 Academic Year. This research is a School Action Research (PTS) which is carried out in 3 cycles, each cycle consists of 2 meetings, so that in total there are 6 meetings. Each cycle is taken in 4 stages, namely planning, action, observation and reflection. The data in this study were collected using observation instruments with checklist instruments, interviews, questionnaires, and journals. Based on the predetermined criteria, it was found that with the implementation of KKG-Based Lesson Study, there was an increase in teacher competence in implementing PAKEM in each cycle in the form of an increase in the mean score, the first cycle got 70, the second cycle increased to 72.83, then in the third cycle it increased to 83.50. This means that the efforts of teachers in implementing PAKEM have been significant. Thus, it can be concluded that the KKG-based Lesson Study can improve the competence of implementing PAKEM for Class Teachers at SDN 4 Sempol, Pagak District, Malang Regency.